The Discursive Construction of the International Community: Evidence from the United Nations General Assembly - Freie Universität Berlin, FB Politik- und Sozialwissenschaften, Otto-Suhr-Institut für Politikwissenschaft Kolleg-Forschergruppe "The Transformative Power of Europe" (2017)
Abstract: The idea that states can hold common values and standards of conduct as well as some capacity to act in the international arena in collective manners for collective goals is epitomized in the concept of international community. Although the term is widely used by scholars, practitioners, and international political leaders and is an integral part of the common international vocabulary, only few have sought to define it, identify its members, and characterize its ways of actions and sources of legitimacy. This paper asks: Who is the international community? Taking a socio-discursive approach, I argue that the international community is essentially a construct that does not exist beyond the discursive level, namely that it materializes only when political agents talk about it, refer to it, and attribute to it certain values, rules, and virtues. I present here the findings of an automated text analysis of 4264 states’ speeches at the United Nations General Assembly (UNGA) that point t